STUDENTS’ DIFFICULTIES IN TRANSLATING NARRATIVE TEXT - Ahmad Nofrian; Syafryadin Syafryadin (PROJECT (Professional Journal of English Education), 2023)
Understanding many kinds of text is very crucial to get much information we are looking for especially narrative text. Narrative text is one of texts that should be mastered by ninth grade students. This study aims to investigate the students’ difficulties in translating narrative text in Empat Lawang schools. The samples of this study are 9 students from SMPN 1, SMPN 2, and SMPN 4 Pendopo Barat. The qualitative method is the method used in the study. The study found 5 difficulties faced by students namely a lack of vocabulary, a lack of idiomatic knowledge, difficulty in locating an appropriate phrase in context, difficulty in understanding whole sentences, and grammatical errors. Therefore, the researcher suggests teachers to identify the best approach to taking on problems like the one in this study. Keywords:  Difficulties; Translating; Narrative Text